One of the causes of the low productivity of rice grown on peat soils was the high levels of of toxic phenolic compounds in the soil. Development of tolerant rice varieties is one of strategies to grow rice on peat soils. The aims of this research were to select rice varieties tolerant to peat soils and to study the correlation between the plant phenolic acid content with plant tolerance to peat soil. This research was conducted at the Seed Farm Centre Lubuk Minturun, Padang from February to Jul - Haryoko, Widodo; Kasli, ,; Suliansyah, Irfan; Syarif, Auzar; Prasetyo, Teguh Budi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
One of the causes of the low productivity of rice grown on peat soils was the high levels of of toxic phenolic compounds in the soil. Development of tolerant rice varieties is one of strategies to grow rice on peat soils. The aims of this research were to select rice varieties tolerant to peat soils and to study the correlation between the plant phenolic acid content with plant tolerance to peat soil. This research was conducted at the Seed Farm Centre Lubuk Minturun, Padang from February to July 2009. The research consisted of two experiments i.e. in peat soil and in mineral soil. The experiments used a completely randomized design using 21 varieties of rice as treatments which were replicated four times. The results showed that there were nine rice varieties categorized as tolerant to peat soil. These tolerant varieties showed higher stress tolerance index (STI), demonstrated by a high level of phenolic acids (coumaric, syringic, and ferulic) in the plant tissues. The STI value had positive correlation with the content of plant phenolic acids, thus the level of plant phenolic acids can be used as an indicator to determine tolerant rice varieties in peat soils. Keywords: peat soil, phenolic acids, tolerant rice, STI